The effects of store environments on customer buying behaviour: a case of the Midlands Spar - Takawira, Kudakwashe (Midlands State University, 2018)
The research investigated the effects of store environments on the buying behavior of customers. Its main objective is to explore the effects of the physical components of the store environment on customer buying behavior. Literature was reviewed guided by given objectives and gaps were noted as the literature flows. The type of research design used in this study was exploratory, making use of a qualitative approach and a communicative technique of interviews. Data collection instruments used in the research includes questionnaires, interviews as well as published documents. Questionnaires targeted customers at Midlands Spar supermarket in Gweru. The researcher used random sampling technique to select the customers in who were shopping at Midlands Spar. Interviews targeted key informants that are the two senior managers at the supermarket. Key informants were selected using purposive sampling. It was found that the physical elements of a store environment which are the ambient factors, designs, people and technology do have the ability to influence consumers in either a subconscious or a conscious way. This had a direct influence on the amount of time that consumers will spend in store and ultimately influences their buying decisions and behaviors either positively or negatively, meaning that the consumers’ will display either an approach- or avoidance behavior.